10-Year patient satisfaction compared between computer-assisted navigation and conventional techniques in minimally invasive surgery total knee arthroplasty. Issue 1 (1st January 2016) - Khuangsirikul, Saradej; Lekkreusuwan, Kreangsak; Chotanaphuti, Thanainit
Abstract: Background: Both minimally invasive surgery (MIS) and computer-assisted surgery (CAS) in total knee arthroplasty have been scientifically linked with surgical benefits. However, the long-term results of these techniques are still controversial. Most surgeons assessed the surgical outcomes with regard to knee alignment and range of motion, but these factors may not reflect subjective variables, namely patient satisfaction. Purpose: To compare satisfaction and functional outcomes between two technical procedures in MIS total knee arthroplasty, namely computer-assisted MIS and conventional MIS procedure, operated on a sample group of patients after 10 years. Methods: Seventy cases of posterior-stabilized total knee prostheses were implanted using a computer-assisted system and were compared to 74 cases of matched total knee prostheses of the same implant using conventional technique. Both groups underwent arthrotomy by 2 cm limited quadriceps exposure minimally invasive surgery (2 cm Quad MIS). At an average of 10 years after surgery, self-administered patient satisfaction and WOMAC scales were administered and analyzed. Results: Demographic data of both groups including sex, age, preoperative WOMAC and post-operative duration were not statistically different. Post-operative WOMAC for the computer-assisted group was 38.94 ± 5.68, while the conventional one stood at 37.89 ± 6.22. The median of self-administered patient satisfaction scales of the computer-assisted group was 100 (min37.5–max100), while the conventional one was 100 (min25–max100). p Value was 0.889. There was one re-operative case in the conventional MIS group due to peri-prosthetic infection which was treated with debridement, polyethylene exchanged and intravenous antibiotics. Conclusions: The 10-year outcomes of computer-assisted MIS total knee arthroplasty are not superior to that of the conventional MIS technique in function and patient satisfaction. 10 years may not be enough to show the difference between these two techniques.